(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The term video compression refers to the process of encoding a video file in a way that resultsin a smaller file size. It can be difficult to record a lengthy video sequence due to the size of the resultingvideo files. An effective motion estimation method in the H.264 encoder has been proposed, together withan optimal dual encryption methodology. In this case, motion estimation is accomplished by acombination of a full search and a diamond search technique. The RSA-based encryption algorithm isencrypted using ECC Rivest-Shamir-Adleman (RSA). Both efficient motion estimation H.264 videocompression are provided by the suggested approach. Compression ratio, PSNR, correlation coefficient,mean absolute error, and pixel change rate are some of the metrics used to evaluate the videocompression technique’s efficacy.